2020
DOI: 10.3389/fchem.2020.00283
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Low-Temperature Hydrogen Storage in Nanoporous Ni-Based Alloy Supported LiBH4

Abstract: To reveal the synergistic effect of nanoconfinement and metallic catalysis on the hydrogen storage properties of LiBH 4 , the nanoporous Ni-based alloy (np-Ni) was prepared herein by dealloying of the Mn 70 Ni 30 alloy in (NH 4) 2 SO 4 solution, and then LiBH 4 was loaded into np-Ni to construct the LiBH 4 /np-Ni hydrogen storage system using wet impregnation. It was found that dehydrogenation of the LiBH 4 /np-Ni (1:5) system starts at around 70 • C and ends before 400 • C, with ∼11.9 wt.% of hydrogen desorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Figure 5 illustrates this statement: if pore filling occurred gradually along the radius (because a LiBH 4 film grew thicker at the interface), then the free pore size measured by nitrogen isotherms would be reduced concomitantly with the pore volume (as observed by Chen et al). 25 The appearance of the isotherm in Figure 2 might suggest an H1-type hysteresis, meaning that the pores are cylindrical. The surface of a tube (2π•r•h) can vary linearly with one of its parameters if the other remains constant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 5 illustrates this statement: if pore filling occurred gradually along the radius (because a LiBH 4 film grew thicker at the interface), then the free pore size measured by nitrogen isotherms would be reduced concomitantly with the pore volume (as observed by Chen et al). 25 The appearance of the isotherm in Figure 2 might suggest an H1-type hysteresis, meaning that the pores are cylindrical. The surface of a tube (2π•r•h) can vary linearly with one of its parameters if the other remains constant.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Chen et al observed that the size of the pore in a nickel porous matrix was lowered from 7.2 to 1.8 nm when the pores were wet impregnated by LiBH 4 (5:1 w/w). 25 This suggests that, depending on the filling method or the matrix nature, the filling of the pores by LiBH 4 might follow very distinct processes. Cahen et al wet impregnated a carbon matrix with LiBH 4 and observed significant differences in the material's behavior; nonetheless, as they did not present the nitrogen adsorption of the infiltrated material, those differences cannot be attributed to the filling method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…% under constant heating at 380 • C in 1 h. Metallic Ti and Ti 3+ species were formed during dehydrogenation, which destabilized the ionic bond between Li + and [BH 4 ] − . Other examples of scaffolds are an Ni-nanoporous alloy and silica MCM-41 [159,160].…”
Section: Other Scaffoldsmentioning
confidence: 99%